Determinants of Mental Illness Among Humanitarian Migrants: Longitudinal Analysis of Findings From the First Three Waves of a Large Cohort Study - Cooper, Sam; Enticott, Joanne C.; Shawyer, Frances; Meadows, Graham (Frontiers in Psychiatry, 2019)
Background: As refugee numbers grow worldwide, understanding prevalence and determinants of mental illness in this population becomes increasingly important. Methods: We used longitudinal data to examine the initial years of resettlement in Australian refugees with a focus on ethnic-like social support. Three annual waves from a longitudinal, nationally representative cohort of 2399 humanitarian migrants recently resettled in Australia were examined for two mental illness outcomes: Posttraumatic Stress Disorder indicated by positive PTSD-8 screen; and ‘High risk of Severe Mental Illness’ (HR-SMI) by Kessler Psychological Distress Scale (K6) ≥19. Generalised linear mixed models examined demographic and resettlement factors. Findings: Contrary to predictions, high prevalence of positive screens for mental illness persisted over 3 years. At baseline, 30·3% (95%CI 28·5-32·2) screened positive for PTSD and 15·4% (95%CI 14·0-16·9) had HR-SMI. Over the 3-years, 52·2% met screening criteria for mental illness. PTSD was associated with older age, females, Middle Eastern birthplace, increasing traumatic events, more financial hardships, having a chronic health condition and poor self-rated health. HR-SMI was associated with females, Middle Eastern birthplace, unstable housing, more financial hardships, having a chronic health condition, poor self-rated health, and discrimination. Also contrary to predictions like-ethnic social support was positively associated with PTSD (OR: 1.51, 95%CI 1·10-2·09). Interpretation: There is high prevalence of positive screens for mental illness throughout initial years of resettlement for refugees migrating to Australia. Our unexpected finding regarding like-ethnic social support raises future avenues for research. Predictors of mental illness in the post-migration context represent tangible opportunities for intervention and are likely relevant to similar resettlement settings globally.